ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN DAN TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Krisyadi, Robby; Elleen, Elleen (Global Financial Accounting Journal, 2020)
The objective of this study is to examine and analyze the correlation of company characteristics and corporate governance towards sustainability report disclosure. The company characteristics mentioned before consist of company size, leverage level, profitability level, and liquidity level, while the corporate governance consist of the board of directors?s meeting frequency and audit committee?s meeting frequency. Companies listed in the Indonesia Stock Exchange from 2014 to 2018 are the objects of this research. Data that needs to be collected are financial reports, annual reports, and sustainability reports if available. Purposive sample is the sampling technique used in this study by establishing certain characteristics that are in line with the objectives of the study. There are 301 companies used as samples. The data that has been collected will then be processed with a software called SPSS Version 22 which is analyzed with the logistic regression model. The test results in this study explain that company size, profitability, and the board of directors have a positive effect on sustainability report disclosure, while leverage and the audit committee don?t have any significant effects on the sustainability report disclosure. In addition, there are also significant negative results indicated by the liquidity variable on the sustainability report disclosure. This is triggered by the company's poor financial condition, so companies with low liquidity tend to disclose more additional information such as sustainability reports so that investors will continue to invest in the company.